PENGARUH POLITICAL CONNECTION DAN MULTIPLE DIRECTORSHIPS TERHADAP EARNINGS MANAGEMENT (Studi pada Perusahaan Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Arif Nugraha; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This study aims to empirically analyze the impact of political connections and multiple directorships on earnings management practices within Indonesian manufacturing companies. Earnings management is a crucial aspect of financial reporting that reflects the effectiveness of corporate governance. Its importance has been underscored by numerous cases demonstrating its potential to distort financial reports, lead to inefficient resource allocation, incite interest conflicts, and attract regulatory sanctions, thus threatening corporate sustainability. Despite the wealth of research on earnings management, the topics of political connections and multiple directorships have received less attention.Indonesia, as a developing country with a complex political system, provides an intriguing context for this study. Several cases, such as Enron, WorldCom, and Bank Century, have shown how political connections can influence earnings management practices and, consequently, corporate sustainability. Similarly, multiple directorships have been linked to corporate governance failures. Yet, the relationship between these factors and earnings management remains inconsistently explored in the literature. This study aims to fill this gap by investigating the influence of political connections and multiple directorships on earnings management using a sample of 38 consumer goods sub- sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. The research employs a quantitative methodology, using secondary data gathered from the Indonesia Stock Exchange and annual company reports. Earnings management was calculated using the Modified Jones Model. The data were analyzed using multiple linear regression with SPSS version 25.The primary findings indicate a positive and significant influence of political connections on earnings management, suggesting companies with political ties tend to engage more aggressively in earnings management practices. However, multiple directorships did not significantly affect earnings management. This research recommends tighter oversight and regulations for politically connected companies and greater transparency in financial disclosures. Further research is encouraged to identify additional factors contributing to earnings management variations.